KEMAMPUAN TANAMAN EKOR KUCING (Typha latifolia) DAN PURUN TIKUS (Eleocharis dulcis) DALAM PENURUNAN KONSENTRASI Fe DAN Mn DARI AIR LIMBAH PIT BARAT PT PAMAPERSADA NUSANTARA DISTRIK KCMB KABUPATEN BANJAR - Muhammad Sulthoni A. D. N.; Badruzsaufari Badruzsaufari; Fadly H. Yusran; Eny Dwi Pujawati (EnviroScienteae, 2014)
Research on the Ability Test Ekor kucing Plants (Typha latifolia) and Purun tikus (Eleocharis dulcis) in Fe and Mn concentrations decrease from the West Pit Wastewater PT Pamapersada District KCMB Kabupaten Banjar. This research held in April 2013 to August 2013. The purpose of this study was to determine the ability of plants Ekor kucing and plants Purun tikus in lowering the concentration of  Fe and Mn from waste coal mine and phytoremediation mechanisms that occur. This research uses experimental and survey methods. Results showed that plants Ekor kucing  and Purun tikus are hiperakumulator plants to Fe and Mn in which the plant is able to absorb Fe respectively by 284% and 92%. For Mn, respectively 207% and 1277%. Phytoremediation mechanisms with Ekor kucing for Fe is fitostabilization  and Purun tikus is fitoextraction, while the Mn is fitoextraction.